PENGARUH PERSEPSI DAN LITERASI TERHADAP MINAT WAKAF UANG PADA MASYARAKAT KECAMATAN TELANAIPURA KOTA JAMBI - Jihan Faadhilah Faadhilah; Novi Mubyarto; Solichah (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
Cash waqf is an Islamic philanthropic instrument that has great potential in supporting the economic development of the community, but its realization level is still far from expectations. This phenomenon is thought to be influenced by public perception factors towards cash waqf and their level of literacy regarding the concept, law, and mechanisms of cash waqf. This study uses a quantitative approach with a survey method. This study aims to analyze the influence of perception and literacy on interest in cash waqf among the people of Telanaipura District, Jambi City. The study population was the Muslim community in Telanaipura District, while the sample was determined using the Slovin formula with a certain margin of error. The research instrument was a questionnaire that measured the variables of perception, literacy, and interest in cash waqf. Data were analyzed using multiple linear regression to determine the effect of each independent variable on the dependent variable. The results showed that perception had a positive and significant effect on interest in cash waqf, which means that the more positive the public's perception regarding the benefits and blessings of cash waqf, the higher their interest in waqf. Similarly, literacy has a positive and significant impact on interest in cash waqf, indicating that the greater the community's understanding of the concept, regulations, and procedures of cash waqf, the greater their intention to participate. Simultaneously, perception and literacy have been shown to significantly influence interest in cash waqf in the Telanaipura District community. This study suggests the need for increased outreach and education regarding cash waqf by relevant institutions to strengthen positive perceptions and improve community literacy, so that the potential of cash waqf can be more optimally realized.